The Role of Leadership and Work Motivation Toward Organizational Citizenship Behavior with Job Satisfaction as Mediation - Mubarokah, Laelaty; Nuvriasari, Audita (Indonesian Journal of Business Analytics, 2023)
This study aims to investigate the impact of leadership and work motivation on Organizational Citizenship Behavior (OCB) by analyzing the role of job satisfaction as a mediator. The research was carried out at the Komite Nasional Pelestarian Kretek (KNPK). The sample size consisted of 45 respondents. The data gathering methodology employed was a survey method, utilizing a questionnaire as the study instrument. The intelligent PLS 3.2 program utilizes sophisticated data analysis techniques like the outer model, inner model, and hypothesis testing. The study findings suggest that leadership does not have a substantial influence on OCB, and job motivation similarly lacks a major impact on OCB. Conversely, work satisfaction has a favorable and substantial impact on OCB. Furthermore, leadership exerts a favorable and substantial impact on job satisfaction, whereas work motivation exerts a favorable and substantial impact on satisfaction. Moreover, job satisfaction serves as a crucial factor in moderating the connection between leadership and Organizational Citizenship Behavior (OCB), as well as between work motivation and OCB.